2020
DOI: 10.1111/jgh.15090
|View full text |Cite
|
Sign up to set email alerts
|

The optimal starting age of endoscopic screening for esophageal squamous cell cancer in high prevalence areas in China

Abstract: did the conception and design of the study. Hao Feng, Guohui Song, and Wenqiang Wei carried out the provision of study materials or patients. Hao Feng,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Our subgroup analysis by age shows that the cumulative incidence rate in elder subjects aged 50 to 69 years had 4.4 times higher than those aged 40 to 49 years. The age 50 was chosen to be the cutoff value according to previous studies associated with ESCC, in which the one‐time endoscopy screening at age 50 years old in resource‐constrained areas may reveal higher detection rate, rendering screening programs cost‐effective 25‐27 . The studies in Japan 28 and Korea 29 also indicated that screening program for GC would be highly cost‐effective when implemented at age 50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our subgroup analysis by age shows that the cumulative incidence rate in elder subjects aged 50 to 69 years had 4.4 times higher than those aged 40 to 49 years. The age 50 was chosen to be the cutoff value according to previous studies associated with ESCC, in which the one‐time endoscopy screening at age 50 years old in resource‐constrained areas may reveal higher detection rate, rendering screening programs cost‐effective 25‐27 . The studies in Japan 28 and Korea 29 also indicated that screening program for GC would be highly cost‐effective when implemented at age 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…The age 50 was chosen to be the cutoff value according to previous studies associated with ESCC, in which the one-time endoscopy screening at age 50 years old in resource-constrained areas may reveal higher detection rate, rendering screening programs cost-effective. [25][26][27] The studies in Japan 28 and Korea 29 also indicated that screening program for GC would be highly cost-effective when implemented at age 50 years. Moreover, consistent with a prior study of ESCC in the same area, older subjects aged 50 to 69 years had three times higher ESCC incidence than younger subjects aged 40 to 49 years.…”
Section: Subgroup Analysis Of Cumulative Gca Incidence and Mortality ...mentioning
confidence: 99%
“…Previous studies showed inconsistent results and were limited due to small sample size and simplistic outcome evaluation. Feng et al found that screening is effective in reducing the mortality of esophageal cancer in 40-49 and 50-59 age group and recommended that people in high prevalence area of esophageal squamous cell carcinoma (ESCC) had one time endoscopy at their 50 years since the 50-59 age group had a lower NNS 13 . Wei et al suggested that the first screening could be postponed to 50 years based on the findings that individuals aged 50-69 years had 3.1 times higher cumulative incidence of ESCC than individuals aged 40-49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited and inconsistent evidence on the optimal starting age for esophageal cancer screening, 13 , 14 the aim of our study was to evaluate the impact of starting age on the effectiveness of screening through comprehensive assessment on multiple outcomes, and to provide high‐quality evidence for optimization and implementation of screening programs in China and other countries with high risk of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%